Analisis Hubungan Jenis Kelamin, Literasi Matematika, dan Disposisi Matematika Terhadap Prestasi Belajar Matematika Peserta Didik SMA Negeri di Denpasar - ., MADE WIDYA SURYAPRANI; ., PROF. DR. I NENGAH SUPARTA, M.Si.; ., PROF.DR.I GUSTI PUTU SUHARTA,M.Si (Jurnal Pendidikan dan Pembelajaran Matematika Indonesia, 2017)
Pembelajaran matematika bertujuan untuk mempersiapkan peserta didik agar dapat menggunakan matematika dan pola pikir matematika dalam kehidupan sehari-hari. Terdapat pandangan di masyarakat bahwa perbedaan jenis kelamin berakibat pada perbedaan kemampuan dalam belajar matematika. Secara spesifik dipercaya bahwa perempuan tidak cukup berhasil mempelajari matematika dibandingkan dengan laki-laki terutama dalam bidang geometri. Selain itu diyakini pula perempuan lebih tertarik pada masalah praktis dan hampir tidak pernah mempunyai ketertarikan yang menyeluruh pada soal-soal teoritis seperti halnya laki-laki. Akan tetapi kenyataan di lapangan menunjukkan bahwa tidak sedikit wanita yang sukses dalam belajar matematika. Penelitian ini bertujuan untuk mengetahui : 1) hubungan antara jenis kelamin dengan kemampuan literasi matematika peserta didik, 2) hubungan antara jenis kelamin dengan disposisi matematika peserta didik, 3) hubungan jenis kelamin, kemampuan literasi matematika, dan disposisi matematika peserta didik dengan prestasi belajar peserta didik. Penelitian ini merupakan penelitian expost facto dengan populasi dalam penelitian ini adalah seluruh siswa kelas X SMA Negeri di Kota Denpasar tahun ajaran 2016/2017 sebanyak 2931 dan diambil sampel dengan teknik multistage random sampling yaitu perwakilan siswa kelas X SMA Negeri di Kota Denpasar tahun ajaran 2016/2017 sebanyak 312 siswa yang terdiri dari 39 siswa di tiap sekolah. Data jenis kelamin diperoleh dari dokumen sekolah, data literasi matematika diperoleh dari tes literasi matematika, data disposisi matematika siswa diperoleh dari pengisian kuisioner, dan data prestasi diambil dari skor UAS semester ganjil 2016/2017 siswa. Data dianalisis menggunakan path analysis dengan menentukan besar koefisien jalur dari model yang dibuat. Hasil analisis data menunjukkan bahwa : 1) Jenis kelamin berkontribusi secara signifikan terhadap literasi matematika siswa dengan besar kontrribusi 30%, 2) jenis kelamin berkontribusi secara signifikan terhadap disposisi matematika siswa dengan besar kontribusi 34%, 3) jenis kelamin, literasi matematika, dan disposisi matematika berkontribusi secara simultan dan signifikan terhadap prestasi belajar matematika siswa dengan besar kontribusi 33,5%.%.Kata Kunci : Jenis Kelamin, Literasi, Disposisi , Prestasi Mathematics learning aim to prepare students to be able to use mathematics and mathematical mindset in everyday life. Gender differences result in differences gaining knowledge of mathematics. Some of the notion that women are not quite managed to learn math than men. In addition, women almost never have a thorough interest in theoretical questions such as the male. Women are more interested in practical matters than the theoretical. But on the other hand, not a few female students who have success in math skills. This study aims to determine at : 1) The relationship between gender and students mathematic literacy skill, 2) the relationship between gender and students mathematic disposition, 3) the relationship between gender, mathematic literacy skill, and mathematic disposition with students mathematics learning achievement of students. This research is expost facto research with population in this research is all students of class X SMA Negeri in Denpasar academic year 2016/2017 as much as 2931 and take sample with multi stage random sampling technique that is representation of student of class X SMA Negeri in Denpasar year 2016 / 2017 as many as 312 students consisting of 39 students in each school. Gender data were collected from school documents, the mathematic literacy data were collected using mathematic literacy skill tests, the disposition mathematic data were collected using observation sheet, and mathematics learning achievement data taken from UAS in odd semester 2016/2017. Analized data using path analysis with determine the path coefficient of the model. The results of the research showed that: 1) Gender contributes significantly to students mathematic literacy by 30%, 2) Gender contributes significantly to students mathematic disposition by 34%, and 3) Gender, mathematic literacy, and mathematic dispositon, simultaneously and significantly on student's mathematics learning achievement with 33.5% contribution.Mathematics learning aim to prepare students to be able to use mathematics and mathematical mindset in everyday life. Gender differences result in differences gaining knowledge of mathematics. Some of the notion that women are not quite managed to learn math than men. In addition, women almost never have a thorough interest in theoretical questions such as the male. Women are more interested in practical matters than the theoretical. But on the other hand, not a few female students who have success in math skills. This study aims to determine at : 1) The relationship between gender and students mathematic literacy skill, 2) the relationship between gender and students mathematic disposition, 3) the relationship between gender, mathematic literacy skill, and mathematic disposition with students mathematics learning achievement of students. This research is expost facto research with population in this research is all students of class X SMA Negeri in Denpasar academic year 2016/2017 as much as 2931 and take sample with multi stage random sampling technique that is representation of student of class X SMA Negeri in Denpasar year 2016 / 2017 as many as 312 students consisting of 39 students in each school. Gender data were collected from school documents, the mathematic literacy data were collected using mathematic literacy skill tests, the disposition mathematic data were collected using observation sheet, and mathematics learning achievement data taken from UAS in odd semester 2016/2017. Analized data using path analysis with determine the path coefficient of the model. The results of the research showed that: 1) Gender contributes significantly to students mathematic literacy by 30%, 2) Gender contributes significantly to students mathematic disposition by 34%, and 3) Gender, mathematic literacy, and mathematic dispositon, simultaneously and significantly on student's mathematics learning achievement with 33.5% contribution.keyword : Gender, Literacy, Disposition, Achievement